EFEKTIFITAS PERLINDUNGAN HUKUM MENGENAI HAK EKONOMI DAN HAK TERKAIT BAGI PENCIPTA MUSIK ATAS TINDAKAN COVER LAGU - Kautsar Dewi Ulayya; Nanik Trihastuti (Universitas Muhammadiyah Ponorogo, 2026)
Social media's purpose has changed from just being a means of communication to being a forum for sharing and publishing copyrighted works, such as music, thanks to its evolution. One illustration of this usage is the use of song covers, which are the re-performance of previously released songs and are common on websites like YouTube. The copyright system legally protects music as an artistic creation, including the economic and related rights of its authors. As evaluated by the implementation of the provisions of Law Number 28 of 2014 on Copyright and the fulfillment of economic rights through royalty payment systems, this study seeks to assess the efficacy of legal protection for the economic rights and related rights of music creators against the practice of song covers on YouTube. The study takes an empirical juridical approach, looking at the laws and how copyright protection is actually implemented in the workplace. The research demonstrates that the government has initiated legal protection measures, such as copyright registration, oversight, and legal support for composers through recognized organizations. The efficiency of such legal protection, however, is mostly contingent on the degree to which cover song artists adhere to their royalty and licensing duties. Consequently, raising digital platform users' understanding of the law is a crucial step toward safeguarding copyright in musical compositions.